Navigating HIV Research among Criminalized Gender Minority Populations in Uganda: qualitative insights and lessons learned from novice researchers - Muwanguzi, Patience A.; Nabunya, Racheal; Ngabirano, Tom D. (International Journal for Equity in Health, 2024)
Transgender individuals often face stigma, discrimination, and various forms of abuse, which negatively impact their mental and physical health. They face a significantly greater risk of HIV, with a higher prevalence than the general population. Despite these challenges, transgender people have limited access to healthcare due to violence, legal barriers, and societal stigma, further exacerbated in countries like Uganda, where transgender identities are criminalized. Therefore, this study explored the lived experiences of HIV researchers working with gender minority populations in criminalizing contexts. This was an interpretative phenomenological analysis (IPA) qualitative study. Twelve (12) research team members at all levels were involved in the study. Participants had less than five years of involvement in HIV research among gender minority populations. Data were collected using field notes, reflective journals, documentation from daily team debriefing sessions, and semi-structured interviews. The analysis used NVivo software. Positive experiences, barriers, and challenges were captured. The positive experiences were ‘respecting cultural diversity’, ‘expanding networks’, ‘addressing misconceptions’ and ‘finding allies’. The barriers included ‘experiencing stigma’, ‘lengthy research processes’, ‘feeling isolated’, ‘fearing for personal safety’, ‘unexpected logistical costs’, and ‘criminalization of sexual and gender minorities’. The key themes that emerged from the lessons learned were: ‘dealing with gatekeepers’, ‘diversity and sensitivity training’, ‘leveraging networks’, ’meaningful community engagement’, ‘reflexivity’, ‘ensuring safety’, ‘equal partnership’, ‘giving feedback’ and ‘awareness of legal implications’. This study highlights the importance of cultural sensitivity, community engagement, and reflexivity in research design and implementation. The findings emphasize the need for innovative strategies to navigate legal, social, and logistical barriers that researchers and participants face. Despite these challenges, the study demonstrates that meaningful collaboration with community members and building trust can significantly enhance the research process and outcomes. Future research should continue to explore these strategies while addressing ethical and safety concerns.